2002
DOI: 10.1086/340797
|View full text |Cite
|
Sign up to set email alerts
|

Measured Mass‐Loss Rates of Solar‐like Stars as a Function of Age and Activity

Abstract: Collisions between the winds of solar-like stars and the local ISM result in a population of hot hydrogen gas surrounding these stars. Absorption from this hot H I can be detected in high resolution Lyα spectra of these stars from the Hubble Space Telescope. The amount of absorption can be used as a diagnostic for the stellar mass loss rate. We present new mass loss rate measurements derived in this fashion for four stars (ǫ Eri, 61 Cyg A, 36 Oph AB, and 40 Eri A). Combining these measurements with others, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
478
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(493 citation statements)
references
References 66 publications
(99 reference statements)
11
478
2
2
Order By: Relevance
“…Spectroscopic analyses of stellar H i Ly-α lines have proven to be the best way so far to clearly detect and measure winds of MS stars like the Sun (Wood et al 2004). In fact, the weak solar-like winds are too hot and thin to provide detectable UV or X-ray absorption (or emission) signatures.…”
Section: Winds From Late-type Dwarfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroscopic analyses of stellar H i Ly-α lines have proven to be the best way so far to clearly detect and measure winds of MS stars like the Sun (Wood et al 2004). In fact, the weak solar-like winds are too hot and thin to provide detectable UV or X-ray absorption (or emission) signatures.…”
Section: Winds From Late-type Dwarfsmentioning
confidence: 99%
“…In a magnetic active star, Ly-α is in emission and its observed profile is the result of the intrinsic stellar line profile with superimposed the absorptions occurring in the stellar astrosphere (the environment around the star similar to the heliosphere that surrounds the Sun), in the LISM, and finally in the heliosphere. By modeling these absorption features, particularly from the properties of the astrosphere model required to fit the line profile, Wood et al (2002) performed the first quantitative measurements of mass loss rates for G and K dwarf stars, and found that the mass loss rates increase with activity (from X-ray surface flux) and thus with decreasing stellar age. From the observed trend of mass loss rate vs. stellar age it results that the solar wind might have been 1000 times stronger when the Sun was very young, and thereby 144 I. Pagano likely played a major role in the evolution of planetary atmospheres, particularly the stripping of volatiles from primitive Mars.…”
Section: Winds From Late-type Dwarfsmentioning
confidence: 99%
“…When solar/stellar winds collide with the interstellar medium, they form, with increasing distance from the star, a termination shock (where the wind is shocked to subsonic speeds), a heliospause (separating the plasma flows from the star and the ISM), and the bow shock (where the ISM is shocked to subsonic speeds). The heliosphere is permeated by interstellar H i with T ≈ (2 -4) × 10 4 K (Wood et al 2002). Much of this gas is piled up between the heliospause and the bow shock, forming the so-called "hydrogen wall" that can be detected as an absorption signature in the Lyα line.…”
Section: The Rotation and Mass-loss History Of The Sunmentioning
confidence: 99%
“…The measurable absorption depths in Lyα are compared with results from hydrodynamic model calculations (Wood et al 2002, Wood et al 2005. The amount of astrospheric absorption should scale with the wind ram pressure, P w ∝Ṁ w V w , where V w is the (unknown) wind velocity (Wood & Linsky 1998).…”
Section: The Rotation and Mass-loss History Of The Sunmentioning
confidence: 99%
“…Its origin is puzzling, as an inner "asteroid belt" that could produce this dust would be dynamically unstable because of the known inner planet (Brogi et al 2009). Here, we check the possibility that the source of the warm dust is the outer ring, from which dust grains could be transported inward by Poynting-Robertson (P-R) drag and strong stellar winds (30 times the solar wind) (Wood et al 2002).…”
Section: Introductionmentioning
confidence: 99%